Constitutive expression of OsDof4, encoding a C(2)-C(2) zinc finger transcription factor, confesses its distinct flowering effects under long- and short-day photoperiods in rice (Oryza sativa L.) - Wu, Qi (BMC Plant Biol, 2017)
BACKGROUND: Dof (DNA binding with one finger) proteins, a class of plant-specific transcription factors which contain a conserved C2-C2-type zinc finger domain, are involved in many fundamental processes. In the Arabidopsis photoperiod response pathway, CDF (CYCLING DOF FACTOR) proteins have a primary role as acting via transcriptional repression of the direct FLOWERING LOCUS T (FT) activator CONSTANS (CO). Our previous study indicated that one of CDF homologs, OsDOf12, was involved in photoperiodic flowering. However, the functional characterization of other rice CDF like genes is still in progress. Here, we characterized the function of OsDof4 in rice. RESULTS: Phylogenic analysis indicated that OsDof4 is closely clustered into the same subgroup with CDFs and OsDof12. The subcellular localization experiment and transcriptional activity assay suggested that OsDof4 may function as a transcription factor. The diurnal expression pattern indicated that OsDof4 was regulated by endogenous circadian clock. Overexpression of OsDof4 led to earlier flowering under natural long-day field conditions (NLDs) and late flowering under natural short-day field conditions (NSDs), respectively. We compared the expression level of key floral genes in vector line and OsDof4-ox lines grown under long-day conditions (LDs) and short-day conditions (SDs). Real-time q-PCR results demonstrated that under LDs, Hd3a, RFT1 and Ehd1 were up-regulated whereas under SDs they were down-regulated. Hd1 was down-regulated at dusk period independent of photoperiods. CONCLUSIONS: Taken these results together, we may speculate that the abnormal flowering responses in OsDof4-ox plants under LDs and SDs might be mediated by Ehd1 and Hd1. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-017-1109-0) contains supplementary material, which is available to authorized users.